(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article “NOMINATION ISSUES IN METALLURGICAL TERMINOLOGY” examines the critical issues of nominative processes in metallurgical terminology, focusing on how technical terms are formed, structured, and standardized within the field of metallurgy. The study emphasizes the importance of systematic and precise term formation, which ensures clarity and mutual understanding among specialists, researchers, and students in the metallurgical sciences. By analyzing both traditional and contemporary approaches to terminological development, the article highlights the interplay between linguistic principles and the practical needs of industry and scientific communication. A central concern of the article is the principle of nominative accuracy, which involves assigning specific, unambiguous names to metallurgical processes, materials, alloys, and equipment. The work demonstrates that proper term formation is not only a linguistic necessity but also a technological imperative, as inaccurate or inconsistent terminology can lead to misunderstandings in production, research, and international collaboration. The study explores the linguistic mechanisms of term creation, including derivation, compounding, abbreviation, and borrowing from other languages, particularly English, Latin, and Russian, which have historically influenced metallurgical vocabulary in Uzbekistan and globally. The article also addresses terminological standardization, investigating the role of international standards and local regulatory frameworks in ensuring that metallurgical terms are coherent, universally recognizable, and adaptable to new technological developments. Special attention is given to the challenges posed by rapid advancements in metallurgical techniques, such as additive manufacturing, alloy design, and high-performance materials, which necessitate the continuous expansion and refinement of the terminological system. Furthermore, the research highlights the pedagogical implications of effective metallurgical terminology. Clear and standardized nomination facilitates technical education, enhances comprehension in higher education curricula, and supports the development of scientific publications and professional documentation. The study argues for an integrated approach that combines linguistic theory, industrial practice, and educational methodology to optimize term formation and usage. In conclusion, the article provides a comprehensive analysis of nominative issues in metallurgical terminology, demonstrating that precise and standardized term formation is crucial for advancing scientific research, technological innovation, and professional communication within metallurgy. It offers insights that are valuable for linguists, educators, industry specialists, and policymakers involved in the development and regulation of technical vocabulary.